THE PHENOMENON OF READING "UNINTENTIONAL" NEWS ON SOCIAL MEDIA (BIBLIOGRAPHY STUDY ON INCIDENTAL NEWS CONSUMPTION) - Suryandini, Dwi Putri (INFOKUM, 2022)
The development of information and communication technology ultimately not only affects people's communication patterns, but also how they consume news/information. Coupled with the emergence of social media, which was originally a space for exchanging news between each other, became an opportunity for news dissemination by professional journalism. Although in the end every user has the opportunity to become a news producer, distributor, or consumer at the same time. This condition then gives rise to accidental exposure to news, which occurs in between its activities on social media based on a system of algorithms determined by the network, or fellow users who share the news. There are three things that are discussed in this article, the first is news on social media, the second is unintentional news, and finally the implications of unintentional news on the understanding of a particular issue, in this case it is a political issue. From the presentation based on previous studies, it is known that accidental news does have an impact on the passivity of social media users to seek information from the main media, which adversely affects a person's knowledge.